Macroeconomics in emerging markets - Montiel, Peter J. (New York : Cambridge University Press, 2003)
Economics
Keywords: Macroeconomics; Macroeconomics and development; Public finance; Macroeconomics performance; Macroeconomic equilibriumFinancial repressiom; Finance, welfare and growth